2015
DOI: 10.1016/j.bbmt.2014.11.447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender: Female Matched Related Donor Versus Male Matched Unrelated Donor on Peripheral Blood Allogeneic Stem Cell Transplant for Male Recipients

Abstract: expansion was reliably achieved when artificial APCs were used. In contrast, when donor PBMCs (without artificial APCs) were used as the source of APCs, 10-100 fold fewer Tregs were obtained. Regardless of protocol, pTregs successfully prevented the proliferation of bead (CD2CD3CD28) stimulated self PBMCs with up to 50% suppression at a 1:32 ratio of Tregs:PBMCs. Contamination of CD8+ T cells was observed despite our efforts to gate out CD8 cells during sorting. Resorting of the Treg cultures early (day 14-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although some prior studies in URDs have found no association between parity and OS, 24 others have demonstrated poorer OS (and higher TRM) in male recipients of female grafts, 31 and yet other analyses have shown improved OS. 32 It is difficult to reconcile the marked differences in survival outcomes in the many studies that have evaluated donor sex or parity, but our large study suggests that if parity is a risk factor for GVHD or other poor outcomes, it is not as significant as the effects of receiving a graft from a URD. Like most transplant analyses, we confirmed that older patient age, poorer patient performance status, advanced disease, and earlier year of transplant were associated with poorer OS.…”
Section: Overall Survival By Donor Groupmentioning
confidence: 90%
“…Although some prior studies in URDs have found no association between parity and OS, 24 others have demonstrated poorer OS (and higher TRM) in male recipients of female grafts, 31 and yet other analyses have shown improved OS. 32 It is difficult to reconcile the marked differences in survival outcomes in the many studies that have evaluated donor sex or parity, but our large study suggests that if parity is a risk factor for GVHD or other poor outcomes, it is not as significant as the effects of receiving a graft from a URD. Like most transplant analyses, we confirmed that older patient age, poorer patient performance status, advanced disease, and earlier year of transplant were associated with poorer OS.…”
Section: Overall Survival By Donor Groupmentioning
confidence: 90%